Improving the Quality of Madrasa Teachers through the Role of the Madrasa Education Service Section at the Ministry of Religion of Muara Enim Regency - Futriana, Ivo; Susilo, M. Joko (Universitas Islam Indonesia, 2022)
Ministry of Religion through the roles of madrasa education services has tried to provide services and guidance to its human resources. This is qualitative research using a phenomenological approach. Researcher focused on strategies, supporting and inhibiting factors, as well as the evaluation of improving the quality of madrasa teachers at the Ministry of Religion in Muara Enim Regency in 2022. Data collection technique used observation, interviews, and documentation. It was then continued with data validity by means of triangulation technique. Once the data were collected, data analysis technique was carried out by going through three stages: data condensation, data presentation and drawing conclusion. In this thesis research, four informants were involved, including one informant as the head of the madrasa education division and other three from teacher representatives in different madrasah. The results showed that: 1) the strategy of improving the quality of madrasa teachers through the roles of the madrasa education division at the Ministry of Religion of Muara Enim Regency was through training programs and workshops; 2) supporting factors included the participation of teachers in adequate coaching, getting a wider range of information, the existence of MGMP (Subject Teacher Consultations), obtaining books relevant to the lesson, and ability to improve the learning process; and 3) the evaluation system in improving the quality of madrasa teachers through the role of the madrasa education division at the Ministry of Religion of Muara Enim Regency was conducted in various ways.